Lupe Wong won't dance - Higuera, Donna Barba (Lantern Paperbacks, 2022)
Baseball is everything to seventh-grader Lupe Wong. So is championing causes, like expanding the options for race on school tests. Lupe has an agreement with her uncle that if she gets straight As in all her classes, she can meet pitcher Fu Li Hernandez, who is half-Mexican, half-Chinese like Lupe. But when the dreaded square dancing unit begins in gym class, Lupe's afraid that she'll never meet Fu Li. As Lupe starts a campaign to get rid of square dancing, her changing friendships force her to reexamine her priorities and relationships.